2023
DOI: 10.1007/s40615-023-01595-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Incentivized Peer Referral to Increase Enrollment in a Community-Based Chlamydia Screening and Treatment Study Among Young Black Men

Abstract: Objectives Young Black men are under-represented in sexual health services and research, a condition likely magnified during COVID-19 shutdowns due to disruption of STI screening and treatment services. We examined the effect of incentivized peer referral (IPR) increasing peer referral among young Black men in a community-based chlamydia screening program. Methods Young Black men in New Orleans, LA, age 15–26 years enrolled in a chlamydia screening program between 3/201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…13 Another study reported that incentivizing peer referrals was an effective means of engaging underrepresented populations in community-based sexually transmitted infection research and prevention programs, noting the particular relevance in contexts where clinic access is limited. 14 While some programs have tested incentives for recipients of adult vaccines, such as influenza and tetanus, diphtheria, and pertussis 15 in addition to COVID-19 vaccination, 16,17 interventions incentivizing individual peer referrals for vaccination are less common. Most of these have been designed for research with key populations for Hepatitis B vaccine or HIV and Hepatitis C vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Another study reported that incentivizing peer referrals was an effective means of engaging underrepresented populations in community-based sexually transmitted infection research and prevention programs, noting the particular relevance in contexts where clinic access is limited. 14 While some programs have tested incentives for recipients of adult vaccines, such as influenza and tetanus, diphtheria, and pertussis 15 in addition to COVID-19 vaccination, 16,17 interventions incentivizing individual peer referrals for vaccination are less common. Most of these have been designed for research with key populations for Hepatitis B vaccine or HIV and Hepatitis C vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Another study reported that incentivizing peer referrals was an effective means of engaging under-represented populations in community-based sexually transmitted infection research and prevention programs, noting the particular relevance in contexts where clinic access is limited. 14 …”
Section: Introductionmentioning
confidence: 99%